Synthesis from D-altrose of (5R,6R,7R,8S)-5,7-dihydroxy-8-hydroxymethylconidine and 2,4-dideoxy-2,4-imino-D-glucitol, azetidine analogues of swainsonine and 1,4-dideoxy-1,4-imino-D-mannitol. - Araújo, N; Jenkinson, S; Martínez, R; Glawar, A; Wormald, M; Butters, T; Nakagawa, S; Adachi, I; Kato, A; Yoshihara, A; Akimitsu, K; Izumori, K; et al. (2012)
Ring closure of a 3,5-di-O-triflate derived from D-altrose with benzylamine allowed the formation of both monocyclic and bicyclic azetidine analogues of swainsonine.